2010
DOI: 10.1073/pnas.1008437107
|View full text |Cite
|
Sign up to set email alerts
|

Role of antigen persistence and dose for CD4+T-cell exhaustion and recovery

Abstract: It is currently not understood how some chronic infections exhaust antigen-specific T cells over time and which pathogen components contribute to exhaustion. Here, we dissected the behavior of primed CD4 + T cells exposed to persistent antigen using an inducible transgenic mouse system that allowed us to control antigen presentation as the only experimental variable, independent of the persistent inflammation and disease progression that complicate infectious models. Moreover, this system restricted antigen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 59 publications
7
127
0
Order By: Relevance
“…Interestingly, following repeated stimulation of OT-II CD4 ϩ T cells in vitro via the TCR, using splenocytes presenting OVA peptide, we also saw less downregulation of T cell function (measured by IL-2 secre- Infection and Immunity tion), without differences in the upregulation of LAG-3 and PD-1 ( Fig. S3), similar to our observations during T cell exhaustion induced by P. yoelii, lending support to the idea that modulation of the response to chronic antigen-specific stimulation of the TCR is central to the role of NFAT1 in the regulation of the T cell exhaustion phenotype (22,23). Increased protection against lethal P. yoelii OVA infection is conferred by adoptive transfer of Nfat1 ؊/؊ CD4 ؉ T cells.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, following repeated stimulation of OT-II CD4 ϩ T cells in vitro via the TCR, using splenocytes presenting OVA peptide, we also saw less downregulation of T cell function (measured by IL-2 secre- Infection and Immunity tion), without differences in the upregulation of LAG-3 and PD-1 ( Fig. S3), similar to our observations during T cell exhaustion induced by P. yoelii, lending support to the idea that modulation of the response to chronic antigen-specific stimulation of the TCR is central to the role of NFAT1 in the regulation of the T cell exhaustion phenotype (22,23). Increased protection against lethal P. yoelii OVA infection is conferred by adoptive transfer of Nfat1 ؊/؊ CD4 ؉ T cells.…”
Section: Resultssupporting
confidence: 78%
“…T-cell exhaustion is common in situations of chronic exposure to antigen, but in immunocompetent mice L. monocytogenes is rapidly cleared (27). Although LLO118 cells do have slight upregulation of PD-1 and CTLA-4, they do not exhibit classic signs of exhaustion, such as dramatically increased levels of PD-1 (28). LLO118 T cells have TCR levels that are down-regulated significantly and for an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…6) also impact on CD8 + T-cell exhaustion. Also in case of CD4 + T cells, it was recently shown that prolonged high-level antigen expression on MHC class II induces CD4 + T-cell exhaustion with the level of antigen exposure influencing the kinetics of CD4 + T-cell dysfunction [46].Unexpectedly, DC-MHCI mice developed disease symptoms after transfer of 10 4 TCR transgenic CD8 + T cells and low-dose LCMV infection, presumably due to their failure to control infection. In addition, DC-MHCI mice succumbed to infection after adoptive CD8 + T-cell transfer and high-dose LCMV infection using CD8 + T-cell numbers where wild-type recipients stayed healthy.…”
mentioning
confidence: 99%